2018
DOI: 10.1177/2280800018784230
|View full text |Cite
|
Sign up to set email alerts
|

BMP-2 and type I collagen preservation in human deciduous teeth after demineralization

Abstract: Background: Great interest has recently been focused on tooth and tooth derivatives as suitable substrates for the treatment of alveolar bone defects. Here, we propose the use of demineralized baby teeth (BT) as potential grafting materials for bone augmentation procedures. Methods: Particles of human BT (Ø < 1 mm) were demineralized by means of a chemical/thermal treatment. Demineralized BT particles were thoroughly characterized by scanning electron microscopy/energy dispersive X-ray analyses to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
(76 reference statements)
0
16
0
Order By: Relevance
“…Both these components have been found to play a key role in the osteoconductive and osteoinductive processes [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…Both these components have been found to play a key role in the osteoconductive and osteoinductive processes [21,23].…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, Bono et al [12] described that deciduous teeth could be used as grafting materials in bone augmentation procedures. They also shed light on the effects of demineralization on deciduous teeth material, evaluating whether or not collagen and BMP-2 protein contents were preserved after the chemical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of endogenous BMP in extracted teeth was very small or nil compared with that of the cortical bone (<1 μg/kg) . Recently, Nina Bono reported that demineralized deciduous tooth contained 1.2 ± 0.3 ng of BMP‐2 per g of tooth particles …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Recently, Nina Bono reported that demineralized deciduous tooth contained 1.2 AE 0.3 ng of BMP-2 per g of tooth particles. 12 The physical properties of dentin, including density, roughness, and homogeneity, and its physiochemical characteristics, including dissolution of calcium/phosphate ions, are similar to those of human cortical bone. 13 Structurally, the dentin matrix consists of dentinal tubules measuring 1-3 μm in diameter with a porosity of 3.70%-5.88% that can be increased by demineralization.…”
Section: Introductionmentioning
confidence: 99%